INFORMATION AND COMMUNICATION TECHNOLOGY AND CREATIVE ECONOMY: A CASE FROM INDRAMAYU - Susri Adeni; Amiruddin Saleh; Musa Hubeis; Arif Satria (Institution: Ministry of Communication and Information Technology of Republic of Indonesia, 2020)
As Indonesian government endorse of growing creative economy, it also relates to the Information and Communication Technology (ICT) which is growing rapidly in Indonesia. The ICT is used by many people in rural area, especially at coastal area. At coastal area most women work for helping the family income. They produce the fish production. Thus it leads to their creativity in producing new product from fish. This creativity should be enforce by utilizing the ICT in particular for enlarging the market. The case from women in Indramayu District specifically in Indramayu sub-district, a coastal area, becomes locus for this research. This paper examines how women at coastal area produce the fish production becoming a creative economy and how they use the internet? The qualitative research is applied in this research. The result show that most women do not really use the internet, only a few of them utilize the internet to market their product by using social media. In conclusion, ICT cannot be applied maximally in Indramayu except the women are obtaining the media literacy.